Resistência do Triatoma brasiliensis ao jejum Resistence of Triatoma brasiliensis to fasting - Maria José Costa; André Luiz Paranhos Perondini (Universidade de São Paulo, 1973)
Triatoma brasiliensis suporta prolongados períodos de jejum em condições de laboratório. O número médio de dias que os animais não alimentados e mantidos a 30oC e a 70-80% U.R. resistiram, foi: 33,30 + 1,12; 44,23 + 1,31; 40,28 + 1,78; 48,00 + 1,56; 58,46 + 3,06; 42,63 + 2,38 e 52,33 + 1,83 para ninfas de 1.°, 2.°, 3.° 4.°, 5.° estádios e adultos, fêmeas e machos, respectivamente. A perda de peso corpóreo durante o jejum é mais drástica na primeira semana decrescendo nas semanas seguintes. Existe diferença nas taxas de perda de peso entre as ninfas do 5.° estádio e os outros estádios estudados. A grande variação na resistência apresentada pelos animais em cada estádio pode ser explicada em termos do peso corpóreo do inseto. A resistência ao jejum aumenta com o aumento de peso podendo, estas relações, serem expressas como funções alométricas. São feitos comentários sobre programas de erradicação. Triatoma brasiliensis can resist to long periods of fasting at a constant temperature of 30 ± 0,5°C and 70-80% RH. The mean number of days the non-fed animals resisted was 33.30 ± 1.12, 44.23 ± 1.31, 40.28 ± 1.78, 48.00 ± 1.56, 58.46 ± 3.06, 42,63 ± 2.38 and 52.33 ± 1.83 for the 1st, 2nd, 3rd, 4th, 5th instar nymphs and adults, femalea and males, respectively. The loss of weight is more drastic in the first week of fasting and gradually decreasis in the next periods. There is a difference in the rate of weight loss during the last weeks of fasting between the 5th instar and the other nymphal and adult stages. The large variation in the number of days each animal survive, in a instar, could be explained by the animal's body weight. Resistence to fasting increasis as the animal's weight increasis, the relationships between these parameters being expressed as allometric mathematical function. Commentaries are made about programs of pest eradication.